2016
DOI: 10.1111/ele.12623
|View full text |Cite
|
Sign up to set email alerts
|

The impact of irradiance on optimal and cellular nitrogen to phosphorus ratios in phytoplankton

Abstract: Phytoplankton acclimates to irradiance by regulating the cellular content of light-harvesting complexes, which are nitrogen (N) rich and phosphorus (P) poor. Irradiance is thus hypothesised to influence the cellular N : P ratio and the N : P defining the threshold between N and P limitation (the 'optimal' N : P). We tested this hypothesis by first addressing the response of the optimal N : P to irradiance in a controlled experiment with Chlamydomonas reinhardtii. Then, we did a meta-analysis of experimental da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…Under low light conditions, growth rates tend to be slower, which would imply lower internal stores of P, but there may be other mechanisms that influence cellular physiology in reduced light conditions. As chlorophyll is rich in N but poor in P, low‐light conditions would also theoretically favor high relative Q N : Q P (Thrane et al ., ). In this study, we found no significant change in stoichiometric ratios with depth (linear regression; R = 0.09, P = 0.76).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Under low light conditions, growth rates tend to be slower, which would imply lower internal stores of P, but there may be other mechanisms that influence cellular physiology in reduced light conditions. As chlorophyll is rich in N but poor in P, low‐light conditions would also theoretically favor high relative Q N : Q P (Thrane et al ., ). In this study, we found no significant change in stoichiometric ratios with depth (linear regression; R = 0.09, P = 0.76).…”
Section: Discussionmentioning
confidence: 97%
“…These factors vary over time and space, and can lead to a wide range of macronutrient cell quotas. In the future, the oceans are expected to undergo increases in temperature, carbon dioxide concentrations and stratification (and thus increased nutrient limitation), which will likely have cascading effects on phytoplankton physiology and the biogeochemical cycles they modulate (see reviews by van de Waal et al, 2009;Finkel et al, 2010). In this future ocean state of higher carbon dioxide, phytoplankton are expected to both increase in biomass (Riebesell et al, 2007) and C:N and C:P ratios (Verspagen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For pelagic autotrophs, however, the stoichiometric responses may be confounded by the aforementioned change in mixing regimes along temperature gradients, and our study on Chlamydomonas suggest no impact at all of temperature on N:P. The chlorophyte Chlamydomonas may, however, not necessarily be representative of responses in other taxa. Different species and taxa of phytoplankton may have different strategies and responses with regard to N and P acquisition together with the N:P ratio of nutrient availability (Klausmeier et al, 2004; Thrane et al, 2016). In a more detailed assay with the same strain of Chlamydomonas grown in microwells along a wide gradient of temperatures and ambient N:P in the media, the optimum N:P ratio shifted from 27 to 37 (atomic ratio) over a temperature gradient from 11 to 18°C (Thrane et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed a similar positive correlation between the overall N:P ratio of marine phytoplankton and global temperature (Martiny et al, 2013; Toseland et al, 2013; Yvon-Durocher et al, 2015), but there are few comparative lake studies, despite the fact that a strong increase in lake temperatures has been recorded worldwide (O’Reilly et al, 2015). A higher N:P with elevated temperature is likely associated with the increased enzyme efficiency at higher temperatures that cause a lower cellular density of P-rich ribosomes because fewer ribosomes are then needed to maintain a certain level of protein synthesis (Toseland et al, 2013; Thrane et al, 2016, 2017). If true, levels of RNA would also be reduced with elevated temperature, but again this response could be confounded by ambient nutrient concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DOM-induced changes in phytoplankton structure and function may be considerable, not only through changes in light availability (Jones, 1998) but also through changes in access to limiting elements such as N, P, and Fe (Elser et al, 2009;Hessen et al, 2009;Molot et al, 2014;Vrede & Tranvik, 2006). Furthermore, the N:P stoichiometry requirements in phytoplankton are affected by light availability, implying that browning influences not only the available nutrient pool but also the required pool; that is, that are necessary for phytoplankton growth (Thrane, Hessen, & Andersen, 2016).…”
Section: Food Qualitymentioning
confidence: 99%